Discrete mathematics with ducks - Belcastro, Sarah-Marie. (Boca Raton : CRC Press, 2012)
'Suitable for an introductory course in discrete mathematics, this textbook has few mathematical prerequisites and does not assume any prior exposure to proofwriting. Still, it covers the standard and practical topics required in a discrete mathematics course and fits the curriculum as outlined in the SIGCSE guidelines, focusing on content rather than technique. Particularly amenable to discovery- or inquiry-based learning, the text includes many exercises and classroom activities, and the author has incorporated instructor's notes at the end of every chapter'--
'An A K Peters book.'
Includes bibliographical references (p. 537-538).
Keywords: Mathematics -- Textbooks; Computer science -- Mathematics